The coiled viper - Abbott, Tony, 1952-; Jessell, Tim.; Copyright Paperback Collection (Library of Congress) (New York, NY : Scholastic Inc., 2003)
Magic on Main Street?!! The border between Droon and the Upper World has been crossed. And now evil Sparr is in Eric's hometown! On a search for the Coiled Viper, he's turning the Upper World inside out. Talking frogs, flying kids, a Ninn parade down Main Street. There's droon magic all over our world! Can Eric and his friends keep it secret?
"A Little Apple paperback."
G2
Keywords: Droon (Imaginary place) -- Juvenile fiction; Fantasy; Friendship -- Fiction; Fantasy fiction